HEAT TRANSFER AND FLUID FLOW INSIDE DUCT WITH USING FAN-SHAPE RIBS - Yousif, Ahmed (Journal of Applied Engineering Science, 2021)
A 2-D computational analysis is carried out to calculate heat transfer and friction factor for laminar flow through a rectangular duct with using fan–shape ribs as a turbulator. The types of rib shapes are imported on the heat transfer rate and fluid flow in heat exchangers. The present study makes use of fan-shaped ribs with two arrangements. The first arrangement was downstream fan–shape ribs (case 1) and upstream fan–shape ribs (case 2) is investigated. A commercial finite volume package ANSYS FLUENT 16.1 is used for solving the meshing process with continuity, momentum, and energy equations respectively to investigate fluid flow and heat transfer across the ribs surface. The Reynolds number (Re) range of (400 – 2250) with different relative roughness pitch (p/H= 0.17, 0.22, 0.27 and 0.32) at constant rib high (e/H). The results show that the heat transfers and friction increase with using ribs also, the results show that heat transfer Directly proportional to pitch ratio and Reynolds number. The Nusselt number enhancement by (12% -29%).
Keywords: heat transfer; fluid flow; fan–shape ribs; Nusselt number; CFD